Penataan Permukiman di Kawasan Benteng Somba Opu Kabupaten Gowa - Ahmad Abdullah Hakim; Mimi Arifin; Wiwik Wahidah Osman (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
The government has established Benteng Somba Opu as a Cultural Heritage Property which should be preserved. The existence of settlements found in the area of ​​Benteng Somba Opu tends to be irregular with the conditions of dense settlements and infrastructure that does not support causing settlements become slums. The objectives of this study are (1) to identify the physical condition of settlements in the Benteng Somba Opu area of ​​Gowa Regency, (2) to identify the social and economic conditions of the community in the Benteng Somba Opu area of ​​Gowa Regency, and (3) to explain the direction of the settlement structuring in the Benteng Somba Opu area of Gowa Regency. Data collection techniques by observation, interviews, questionnaires, documentation and literature studies. The analysis used is descriptive analysis, spatial analysis and comparative analysis. The results showed that, (1) the number of buildings in the study site were 949 units, consisting of 518 permanent buildings, 220 semi-permanent buildings, and 211 semi-permanent buildings. The condition of facilities and infrastructure is inadequate, especially clean water and solid waste systems. (2) the level of public education is still low where 34.44% of respondents only graduated from elementary school, while community work is dominated in the service sector as much as 45.56% and laborers as much as 26.67%. (3) the improvement of the quality of settlements in the Benteng Somba Opu area is directed to the restoration and resettlement by making rental apartments in a location close to the Benteng Somba Opu area.